A Correlation Betwen Self Confidence And Oral Speaking Ability (A Study At The Third Semester In Stkip “Tapanuli Selatan” Padangsidimpuan In 2013/2014 Academic Year) - Habib Rahmansyah (Institut Pendidikan Tapanuli Selatan, 2016)
In doing the research, the writer analyzes the correlation between self confidence and oral speaking ability. Thepurposes of this research are to find out: 1) The extent of the students‟ ability in oral speaking at the third semester studentsin STKIP Tapanuli Selatan Padangsidimpuan, 2) The extent of the students‟ self confidence at the third semester students inSTKIP Tapanuli Selatan Padangsidimpuan, 3) whether there is significant correlation between self confidence and oralsepaking ability at the third semester students in STKIP Tapanuli Selatan Padangsidimpuan that consist of 215 students. Thesamples are 40 students taken by cluster sampling. This research uses descriptive method. In collecting data the writer usestest as instrument. The data are analyzed by using the formula of “r Product Moment”. After analyzing the data, it can beconcluded that the students‟ self confidence is categorized “enough‟ which mean score is 62.4 and oral speaking ability is64.7 that is categorized “enough”. Then the score of “r”calculation is obtained 0.641. It is higher than the score of “r” tab le(0.641 > 0.320). It means that there is a significant correlation between self confidence and oral speaking ability at the thirdsemester students in STKIP Tapanuli Selatan Padangsidimpuan means or the hypothesis is accepted.